Keragaman Mikroalga di Lahan Bekas Tambang Batubara, Cempaka - Gunawan Gunawan (Universitas Lambung Mangkurat, 2011)
Have been by research the diversity of microalgae, at quarry Banjarbaru, with Purposive Random Sampling method in three stations, that there quarry 1, quarry 2 and quarry 3. The result showed that 32 genera fitoplankton which category into 5 classes include: Chlorophyceae, Chrysophyceae, Rhocophyceae, Xanthophyceae, Bacillariophyceae. The highest index of diversity was quarry 2 and lowest index diversity was quarry 3. Correlations analysis test indicate that pH were signivicant to the diversity of fitoplankton.